Preoperative CT versus diffusion weighted magnetic resonance imaging of the liver in patients with rectal cancer; a prospective randomized trial - Michael P. Achiam; Vibeke B. Løgager; Bjørn Skjoldbye; Jakob M. Møller; Torben Lorenzen; Vera L. Rasmussen; Henrik S. Thomsen; Talie H. Mollerup; Cecilie Okholm; Jacob Rosenberg (PeerJ, 2016)
Introduction. Colorectal cancer is one of the most frequent cancers in the world and liver metastases are seen in up to 19% of patients with colorectal cancers. Detection of liver metastases is not only vital for sufficient treatment and survival, but also for a better estimation of prognosis. The aim of this study was to evaluate the feasibility of diffusion weighted MRI of the liver as part of a combined MR evaluation of patients with rectal cancers and compare it with the standard preoperative evaluation of the liver with CT.Methods. Consecutive patients diagnosed with rectal cancers were asked to participate in the study. Preoperative CT and diffusion weighted MR (DWMR) were compared to contrast enhanced laparoscopic ultrasound (CELUS).Results. A total of 35 patients were included, 15 patients in Group-1 having the standard CT evaluation of the liver and 20 patients in Group-2 having the standard CT evaluation of the liver and DWMR of the liver. Compared with CELUS, the per-patient sensitivity/specificity was 50/100% for CT, and for DWMR: 100/94% and 100/100% for Reader 1 and 2, respectively. The per-lesion sensitivity of CT and DWMR were 17% and 89%, respectively compared with CELUS. Furthermore, one patient had non-resectable metastases after DWMR despite being diagnosed with resectable metastases after CT. Another patient was diagnosed with multiple liver metastases during CELUS, despite a negative CT-scan.Discussion. DWMR is feasible for preoperative evaluation of liver metastases. The current standard preoperative evaluation with CT-scan results in disadvantages like missed metastases and futile operations. We recommend that patients with rectal cancer, who are scheduled for MR of the rectum, should have a DWMR of the liver performed at the same time.